2015
DOI: 10.1007/s10461-015-1269-6
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Self-Reported Condom Use: Association Between Over-Reported Condom Use and Syphilis in a Three-Site Study in China

Abstract: This study examined over-reporting bias in self-reported condom use and assessed its association with syphilis. A survey was conducted among 1245 female sex workers (FSWs) in three cities in China. Respondent’s over-reported condom use was defined as reporting no unprotected sex for the past 24 h but testing positive for prostate specific antigen. The proportion of prevalent syphilis and active syphilis was 23 and 10 % respectively among FSWs. The proportion of over-reported condom use with sex clients only wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…These findings imply that the Chinese health authorities need to pay attention to implementing intervention programs not only in geographic areas with higher HIV/STI epidemics, but also in areas with small-scale epidemics. 49 There are some limitations in this study. First, the crosssectional nature of the survey does not allow us to identify 162 LIU casual relationships because of potential temporal ambiguity bias.…”
Section: Discussionmentioning
confidence: 91%
“…These findings imply that the Chinese health authorities need to pay attention to implementing intervention programs not only in geographic areas with higher HIV/STI epidemics, but also in areas with small-scale epidemics. 49 There are some limitations in this study. First, the crosssectional nature of the survey does not allow us to identify 162 LIU casual relationships because of potential temporal ambiguity bias.…”
Section: Discussionmentioning
confidence: 91%
“…The study methods have been previously described in detail (36, 45) The study protocol was approved by the Institutional Review Boards of the University of Maryland, Shandong University School of Public Health, and the Centers for Disease Control and Prevention in Hefei and Guangxi. Written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies linking misreported sexual activity to STIs are mixed (9,11,14). These inconsistencies may stem from different definitions of discordance, including using self-reported condom use instead of sexual activity.…”
Section: Introductionmentioning
confidence: 97%
“…However, with the advent of biological measures, such as the PSA test, several studies in different populations of sex workers have revealed that condom use may be inaccurately reported (912) and that bias exists regardless of the interview mode (e.g., face-to-face interviews, audio computer assisted self-interviewing, and computer assisted self-interviewing) (13). Additionally, our previous study demonstrated that a substantial proportion of FSWs over-reported their condom use and that this over-reporting was associated with syphilitic infection (14). …”
Section: Introductionmentioning
confidence: 99%